Topological insulators: Engineered heterostructures - Hesjedal, T; Chen, Y (Nature Publishing Group, 2016)
The combination of topological properties and magnetic order can lead to new quantum states and exotic physical phenomena. In particular, the coupling between topological insulators and antiferromagnets enables magnetic and electronic structural engineering.